Motives and Manipulative Strategies on COVID-19 Discourse in Indonesia - Waki Ats Tsaqofi; Sarah Hajar Mahmudah (Mimbar Agama dan Budaya, 2023)
This study delves into examining manipulative strategies within the framework of COVID-19 discourse in Indonesia. The research systematically analyzes data from various social media platforms using a descriptive qualitative methodology. The analytical framework draws from speech act theory, argumentative discourse approaches, and manipulation strategy theory. The study’s findings uncover various manipulative tactics that influential figures in Indonesia deploy. These tactics encompass denial, rationalization, diversion, lying, guilt-tripping, and shaming. Notably, the research offers tangible instances of manipulation within the COVID-19 discourse, such as claims suggesting that the virus represents a divine army or that Chinese individuals frequent mosques to learn ablution (wudu). This study is valuable to the expanding literature on COVID-19 discourse and manipulation. It offers nuanced insights into the strategies harnessed to sway public opinion amid a global pandemic. The discerned findings from this study hold significant potential, as they can inform the development of public awareness campaigns and strategies designed to counter the spread of misinformation and disinformation, a critical endeavour in today’s information-rich landscape.